Physicochemical quality, antioxidant compounds and activity of MD-2 pineapple fruit at five ripening stages - Ding, Phebe; S., Syazwani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Although Malaysia is one of the important pineapple fruit producing and exporting country, the production of MD-2 pineapple fruit only started in 2009. Pineapple fruit has been harvested at different ripening stages for different markets. The information on Malaysian grown MD-2 pineapple fruit quality is lacking. Therefore this work was carried out with the aim to determine physicochemical quality, antioxidant compounds and activity of MD-2 pineapple fruit at five ripening stages. Ripening stage affected physicochemical quality of MD-2 pineapple fruit. Soluble solids concentration of MD-2 pineapple fruit increased from 15.41 to 18.02%SSC when fruit ripened from stage 1 to 4 and no significant difference was found in fruit between stage 4 and 5. The ascorbic acid content decreased while total carotenoids content increased as ripening stage advanced. The total phenolic content of both 80% methanol and water extraction solvents increased significantly as fruit ripened from stage 1 to 3 and reduced as fruit ripened to stage 5. The antioxidant activity of MD-2 pineapple fruit as assayed using DPPH, FRAP and ABTS showed similar trend as total phenolic content. These results suggest that ripening stage affect MD-2 pineapple fruit quality and nutritional values.